Contested governance : culture, power and institutions in indigenous Australia - Hunt, Janet (Research monograph (Australian National University. Centre for Aboriginal Economic Policy Research), 2008)
"The research in this book aims to provide evidence and practical guidance for governments and Indigenous leaders about community governance in indigenous Australia, and contribute to enhancing existing success. This book documents many of the challenges, opportunities and issues facing those engaged in trying to achieve legitimate and effective governance on the ground. It considers the significant underlying problems that have to be resolved if indigenous social and economic development is to be achieved and sustained."--Information provided by publisher